The presence of carcinogenic radon in the Padma River water, adjacent to the Rooppur Nuclear Power Plant - M.M. Mahfuz Siraz; M.S. Alam; A.M. Jubair; S.C. Das; J. Ferdous; Z. Hossain; S. Das; Mayeen Uddin Khandaker; D.A. Bradley; Shinji Tokonami; S. Yeasmin (Nuclear Engineering and Technology, 2023)
Radon is a naturally occurring carcinogenic agent, poses a serious health hazard when inhaled or ingested in significant amounts. The water of the Padma river will be used as a tertiary coolant for the soon-to-be-commissioned ‘Rooppur Nuclear Power Plant’. Hence, it is important to assess the radiological status of the river prior to the commission of this power plant. Therefore, for the first time, 25 samples of water were collected from various locations of the Padma River and analyzed for radon concentration using the RAD H2O (DURRIDGE) radon monitoring device. The radon concentrations were found in the range from 0.077 ± 0.036 to 0.494 ± 0.211 Bq/L with a mean of 0.250 ± 0.093 Bq/L. All the concentrations were found to be below the recommended limits of WHO (100 Bq/L) and USEPA (11.1 Bq/L). The mean annual effective dose due to the radon exposure via inhalation and ingestion pathways were 0.638 μSv/y and 0.629 μSv/y, respectively, which were all well below the annual effective dose recommended by WHO (0.1 mSv/y). Since Bangladesh lacks a national safety limit of radon in water, this pioneering study provides baseline data on radon levels for the environment around Rooppur Nuclear Power Plant.